EGGS RELEASED BY THE NOTOTHENIID FISH TREMATOMUS BERNACCHII BOULENGER IN CAPTIVITY (Eleventh Symposium on Polar Biology) - コンドウ, ヨシタカ; サカキバラ, シゲル; トバヤマ, テルオ; ホシアイ, タカオ; KONDO, Yoshitaka; SAKAKIBARA, Shigeru; TOBAYAMA, Teruo; HOSHIAI, Takao (National Institute of Polar Research, 1990)
P(論文) In the morning of 24 April 1988, eggs were released by a single fish of the nototheniid Trematomus bernacchii which were reared in an aquarium of the Kamogawa Sea World, Chiba Prefecture, Japan. The 4811 eggs were liberated on sand. Eggs were adhesive, semi-transparent, milk-white in color, and 4.4-4.7 mm in diameter. The 1988 results were compared with those of the preceding 4 years. departmental bulletin paper